Soldiers of the Pen : The Writers' War Board in World War II - Howell, Thomas, 1944- (Book collections on Project MUSE., 2019)
"From 1942 to 1945, a small, influential group of media figures willingly volunteered their services to form the Writers' War Board (WWB), accepting requests from government agencies to create propaganda. Members included mystery writer Rex Stout, Pulitzer and Nobel Prize winner Pearl S. Buck, novelist and sports writer Paul Gallico, Book-of-the-Month Club editor and popular radio host Clifton Fadiman, and Broadway lyricist Oscar Hammerstein II. The WWB mobilized thousands of other writers across the country to spread its campaigns through articles, public appearances, radio broadcasts, and more. The WWB received federal money while retaining its status as a private organization that could mount campaigns without government oversight. Historian Thomas Howell argues that this unique position has caused its history to fall between the cracks, since it was not recognized as an official part of the government's war effort. Yet the WWB's work had a huge impact on the nation's wartime culture, and this fascinating history will inform contemporary thinking on propaganda, the media, and American society." -- Publisher's description